Lycksalighetens källa : kontextuella närläsningar av Anders Chydenius budordspredikningar, 1781-82 - Nordbäck, Carola, 1963-; Åbo Akademis förlag (Åbo : Åbo Akademi University Press ; distribution: Pargas : Tibo-trading, 2009)
Summary: The source of blessedness : a contextual close reading of the catechetical sermons on the Ten commandments of Anders Chydenius, 1781-82.
Väitöskirja
K-KPL
Keywords: Chydenius, Anders, -- 1729-1803.; 1700-luku; saarnat; homiletiikka; aiheet; käskyt; luterilaisuus